2022
DOI: 10.7150/thno.71873
|View full text |Cite
|
Sign up to set email alerts
|

Spatial maps of hepatocellular carcinoma transcriptomes reveal spatial expression patterns in tumor immune microenvironment

Abstract: Rationale: Hepatocellular carcinoma (HCC) is a highly heterogeneous and malignant disease with the complex immune microenvironment, which ultimately influence clinic outcomes of patients. However, the spatial expression patterns of diverse immune cells among tumor microenvironment remain to be further deciphered. Methods: Spatial transcriptomics sequencing (ST) was implemented on two portions of HCC specimens. Differentially expressed genes, cell cycle phases, epithelial-mese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 57 publications
0
18
0
1
Order By: Relevance
“…The Visium Spatial Gene Expression Slide and Reagent Kit (10 × Visium) were used to process the spatial gene expression data. 77 , 78 To prepare the sections for gene expression analysis, they were incubated with permeabilization enzyme for 20 min at 37°C for pre‐permeabilization. After washing the sections with saline sodium citrate, a reverse transcription master mix was added to synthesize cDNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Visium Spatial Gene Expression Slide and Reagent Kit (10 × Visium) were used to process the spatial gene expression data. 77 , 78 To prepare the sections for gene expression analysis, they were incubated with permeabilization enzyme for 20 min at 37°C for pre‐permeabilization. After washing the sections with saline sodium citrate, a reverse transcription master mix was added to synthesize cDNA.…”
Section: Methodsmentioning
confidence: 99%
“…The tissue blocks were cryosectioned at a thickness of 10 μm and attached to the capture areasbefore proceeding to the next step, followed by H&E staining. The Visium Spatial Gene Expression Slide and Reagent Kit (10 × Visium) were used to process the spatial gene expression data 77,78 . To prepare the sections for gene expression analysis, they were incubated with permeabilization enzyme for 20 min at 37°C for pre‐permeabilization.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that M2 macrophages, CAFs, and some T lymphocytes were always located in the center of the tumor, and these T lymphocytes were identified as exhausted CD8+T cells [57] and unconventional CD4+T cells [58]. Exhausted CD8+T cells are often found in cancers, which are a type of T cell lacking effector functions [59], and the unconventional CD4+T cells are a type of T cell subtype similar to regulatory T cells [60], which are related to the immunosuppressive and tissue repair systems [58,61]. These two cell types are very close to the localization of M2 macrophages and CAFs, thus they might be regulated by these tumor-related stromal and myeloid cells, resulting in loss of their anti-tumor functions to help tumor cells escape immune response.…”
Section: Spatial Transcriptomic Sequencing In Whole Tissue Sectionsmentioning
confidence: 99%
“…In ICC, hepatocytes close to invasive fronts with high expression level of SAA1 and SAA2 were correlated with worse prognoses ( 19 ). Moreover, many gene markers were identified in PDAC, liver cancer, BC, bladder cancer, SCC and GC ( 53 , 92 , 112 , 114 , 121 , 126 , 133 ). Cell subpopulations were also potential markers of prognosis.…”
Section: Clinical Application Of Stmentioning
confidence: 99%